Nursing audit: profissionals’ knowledge in a public hospital of reference - Maria Leonice de Lima Passos; Carmina Teixeira Borges; Maria Beatriz de Paula Tavares Cavalcante; Maria Glêdes Ibiapina Gurgel; Maria Sueuda Costa; Maria Dalva Santos Alves (Rev Rene)
Nursing audit is the assessment of the quality of care provided, which benefits the patient as much as the nursing team and the institution. We aimed to identify the knowledge of the nurses on the audit process. Exploratory, descriptive and quantitative study that was carried out from September to December 2007, with participation of 36 nurses of a public hospital of reference for cardiovascular illnesses, in Fortaleza, Ceará, Brazil. A self-answered survey was used with questions about the knowledge of the participant on the concept, the purpose and the benefits of nursing audit. The results were classified according to knowledge level, following the specific literature adopted in the study. The perception of the study participants showed to be limited, demonstrating little knowledge on the theme, suggesting the need to better invest in the professional formation, seeking to awake the importance of nursing audit.